Implementasi Kualitas Pelayanan Transjakarta Cares Untuk Mewujudkan Kota Inklusif Di DKI Jakarta - Rana Fakhira; Mutiara Juliahisa Doneriani; Ninis Mu’Tadilah; Sheila Puspita Kusumawati (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The implementation of E-government in Indonesia is currently still being accelerated in order to realize the creation of Good Government. All aspects needed to implement E-government continue to be improved, including the E-procurement sector. Transjakarta cares is one of the service programs provided by Transjakarta which aims to make it easier for people with disabilities in DKI Jakarta to use public transportation. This service aims to make DKI Jakarta an inclusive city which means DKI Jakarta is a livable province for all people, including people with disabilities. This research was conducted by means of a literature study by taking data from literacy sources. This breakthrough service carried out by Transjakarta has received a lot of support from various parties, including the private sector. Support in the form of assistance has been carried out, such as providing vehicles for implementation to revitalizing access to bus stops carried out by the regional government to make it easier for users of Transjakarta cares services. The coverage area that can be accessed by Transjakarta cares is already quite good and is currently being expanded so that all residents in the DKI Jakarta area can use Transjakarta cares services.